Tanggung Jawab Sosial Perusahaan dan Kesejahteraan Anak: Studi Literatur pada Program CSR di bidang Pendidikan dan Kesehatan - Dyta Mardyani; Santoso Tri Raharjo (Politeknik Kesejahteraan Sosial Bandung, 2023)
Abstract Problems that can affect children's welfare are still rife. Education and child health issues are still issues that are quite common in Indonesia. The issue of education and health can affect the welfare of a child, because education and health are included in the rights of the child and must be fulfilled by the child. If the child's rights cannot be fulfilled, it will affect the welfare of the child. The achievement of child welfare can occur when the basic needs and rights of children can be fulfilled (Fitri et al., 2015). One of the efforts to overcome children's issues can be done through Corporate Social Responsibility. Schermerhorn (1993) in (Rizky et al., 2015) suggests Corporate Social Responsibility as a form of corporate concern to act in their own way in serving the interests of the organization and the wider community. Writing this article aims to determine the company's involvement in responding to issues of education and child health through the CSR Program. The method used in writing this article is library research. Based on the literature that has been conducted, it is known that quite a number of companies have established CSR programs based on education and child health issues, such as the SEHATI program conducted by PT. Pertamina, which focuses on toddler health, educational assistance in the form of scholarships and the construction of school buildings carried out by PT Semen Indonesia, and the Scholarship Program for Children of Farmers to Become Graduates conducted by PT Pusri Palembang. Keywords: Educational Problems, Child Health Problems, Child Welfare, Corporate Social Responsibility, and Children's Rights.